This time it's different? Effects of the Eurovision Debate on young citizens and its consequence for EU democracy – evidence from a quasi-experiment in 24 countries. Issue 4 (3rd April 2018) - Maier, Jürgen; Faas, Thorsten; Rittberger, Berthold; Fortin-Rittberger, Jessica; Josifides, Kalliope Agapiou; Banducci, Susan; Bellucci, Paolo; Blomgren, Magnus; Brikse, Inta; Chwedczuk-Szulc, Karol; Lobo, Marina Costa; Cześnik, Mikołaj; et al.
ABSTRACT: For the very first time in EU history, the 2014 EP elections provided citizens with the opportunity to influence the nomination of the Commission President by casting a vote for the main Europarties' 'lead candidates'. By subjecting the position of the Commission President to an open political contest, many experts have formulated the expectation that heightened political competition would strengthen the weak electoral connection between EU citizens and EU legislators, which some consider a root cause for the EU's lack of public support. In particular, this contest was on display in the so-called 'Eurovision Debate', a televised debate between the main contenders for the Commission President broadcasted live across Europe. Drawing on a quasi-experimental study conducted in 24 EU countries, we find that debate exposure led to increased cognitive and political involvement and EU support among young citizens. Unfortunately, the debate has only reached a very small audience.